Phenotypic evaluation of antimicrobial susceptibility of Vibrio spp. isolated from white shrimp (Penaeus vannamei) from Tumbes, Peru - Rosado S., Armando (2025)
The study evaluated the resistance of presumptive Vibrio isolates to antibiotics important for both aquaculture and human health. Isolates were identified biochemically, using sugar (sucrose) fermentation. The susceptibility profile was tested using the agar diffusion technique against active ingredients representing five groups of antibiotics. Of the 57 isolates, six Vibrio species were identified. Resistance to ampicillin (aminopenicillin) was observed in 47% of the isolates, followed by chloramphenicol (amphenicol) in 19%, and to tetracycline (tetracycline) in 16%. The most effective drugs were sulfamethoxazole- trimethoprim (95% of susceptible isolates and 3% of resistant isolates) and ciprofloxacin (fluoroquinolone) (93% of susceptible isolates and 0% of resistant isolates). It is concluded that antimicrobial resistance in shrimp aquaculture in Tumbes, Peru, does not pose a risk to public health, but should be monitored through longitudinal evaluations.